Development of Car Tyre Air Pressure System (CTAPMS) Using Node MCU ESP8266 Board - Mohd Isha, Mohamad Faris; Joret, Ariffuddin; Sulong, Muhammad Suhaimi (Journal of Sustainable Manufacturing in Transportation, 2022)
CTAPMS is an electronic system designed in this work to monitor the air pressure inside pneumatic tyres on various types of vehicles. A crucial issue in monitoring air pressures of a tyre was most users are too lazy and do not check their car tyre condition daily or before starting a journey. As an assist device for the user to monitor their car air tyre pressure daily, this project has developed the CTAPMS using a BMP180 sensor and Node MCU 8266 microcontroller board. Based on the system, the measured car air tyre pressure can be visualized from the ThingSpeak IoT platform through a smartphone. The performance of the developed system has been validated through a series of experimental works. The result indicates a reliable measurement with an error of less than 10% as compare to the existing system. Further, this product will be commercialized for future use.